Granting Business License to Fuel Traders “Pertamini” As a Form of Legal Protection - Nirwan Junus; Karlin Zakaria Mamu; Mohamad Syahnez W. Aditya Cono (Jambura Law Review, 2021)
Oil and Gas plays an important role in the fulfillment of fuel needs from both the industrial and transportation sectors. This regulation on Oil and Gas has provided a legal basis in its implementation.  The presence of retail fuel businesses "Pertamini" is causing legal problems, this is because the existence of these businesses do not have a formal business license at all.This paper analyzes the sale of fuel under the brand "Pertamini" which does not have a business license. This research uses normative legal research method with statute approach and conseptual approach.The results showed that, with the increasing number of "Pertamini" fuel traders without a license, it will certainly have implications for the law and uncontrolled management of Oil and Gas. Therefore, the government and related agencies can issue permits to "Pertamini" fuel traders. Because by obtaining a legal business license, in terms of its management can be carried out optimal supervision to prevent the occurrence of fuel misuse. This also includes efforts to provide certainty and legal protection to "Pertamini" Fuel Traders.